MENEGUHKAN SIKAP TABAYYUN DALAM MENGHADAPI HOAKS DI MEDIA SOSIAL - Falihah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The rapid advancement of digital technology and the massive use of social media in Indonesia have led to the widespread dissemination of hoaxes. These false information pose significant risks, including social conflict and public unrest. Therefore, this study aims to reinforce the attitude of tabayyun (verification/cross-checking) as an Islamic ethical principle to counter hoaxes on social media. Using a qualitative literature review approach, this research examines the concept of tabayyun derived from Surah Al-Hujurat verse 6 and its relevance in the digital era. The findings indicate that tabayyun serves as a crucial filter in receiving and sharing information. It involves assessing information quality, verifying sources, comparing data, and enhancing digital literacy. The study concludes that cultivating and strengthening tabayyun is essential for every Muslim to avoid being trapped by false news. Proposed solutions include source verification, information comparison, and continuous self-education. By internalizing tabayyun, individuals can act more cautiously and responsibly in the digital public sphere.